2009
DOI: 10.3339/jkspn.2009.13.1.56
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Protein and Enzyme Excretion of Spot Urine in Children with Vesicoureteral Reflux

Abstract: The aim of this study was to evaluate the clinical usefulness of measurement of β 2 microglobulin (β 2 MG), N-acetyl-β-D-glucosaminidase (NAG) of spot urine samples as indices of renal tubular damage and microalbumin of spot urine samples as a parameter of glomerular damage in children with vesicoureteral reflux (VUR) or renal defects. Methods : We studied 91 children with previous UTI. The children were classified as 62 children without VUR and renal defects (group I), 10 children with VUR, without renal defe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
1

Year Published

2010
2010
2013
2013

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 19 publications
0
5
1
Order By: Relevance
“…In this study VUR, VUR grade, renal parenchymal defect and renal scar were not correlated to microalbuminuria. The discrepancy between the findings reported in our study and reported by Yoon et al 5) is likely due to difference of mean age of patients, severity of disease. Therefore further longitudinal follow-ups are required to confirm the apparent absence of correlation.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…In this study VUR, VUR grade, renal parenchymal defect and renal scar were not correlated to microalbuminuria. The discrepancy between the findings reported in our study and reported by Yoon et al 5) is likely due to difference of mean age of patients, severity of disease. Therefore further longitudinal follow-ups are required to confirm the apparent absence of correlation.…”
Section: Discussioncontrasting
confidence: 99%
“…Few study investigated spot urine microalbumin/creatinine ratio in children 5 , 6) . Several prior reports indicated that spot urine samples provide a good estimate of the 24-hour excretion rate 20 , 21) .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…92 Urinary microalbumin excretion may be a useful marker to predict the severity of VUR. 93 There is an insignificant increase of microalbuminuria and decrease of creatinine clearance in children with a high grade of VUR, as a possible consequence of retrograde urine flow (intrarenal reflux), glomerulosclerosis, and consecutive hyperfiltration. 94 The spot urine microalbumin/creatinine ratio is significantly increased in children with previous UTI and VUR.…”
Section: Risk Factorsmentioning
confidence: 99%